Lithium metal oxides (metal = manganese, chromium, cobalt, or aluminium) as cathode in lithium ion battery [compact disc] - 416581 Md. Mokhlesur Rahman (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2006